Asistensi Mengajar Melalui Program Surabaya Mengajar Pada SMP Negeri 39 Surabaya - Maulida, Meilani Nur (Universitas Gajah Putih, Indonesia, 2023)
The Surabaya Mengajar program is part of the Merdeka Learn Kampus Merdeka (MBKM) policy to enrich student competencies by providing opportunities for students to learn outside the classroom by providing assistance to teachers and education staff at the basic education level. The Surabaya Teaching program is currently the third cohort assigned to teach, and assist with school administration and teachers in schools. Oneof the schools where Surabaya teaches is SMP Negeri 39 Surabaya.In practice, Surabaya Teachingstudents use severalmethods,startingfrom debriefing/coordinating, visiting the local regional Education Office, to visiting the destination school to make observations.The results of the implementation of the Surabaya Teaching program batch 3 in teaching assistance that have been carried out by students at SMP Negeri 39 Surabaya are in accordance with the achievement of the objectives of the Surabaya Teaching program batch 3 through the introduction of literacy and numeracy to students in target schools; create innovation and creativity by collaborating with teachers in schools to jointly improve the quality of education in target schools; hone skills and insights in the field of teaching and also develop learning media that can be applied directly to students to support the learning process in class; develop rational and targeted thinking patterns in working with teams, solving problems within the scope of work, as well as controlling emotions in a social environment outside the world of lectures.